If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(10y + -6) = -5 Reorder the terms: 4(-6 + 10y) = -5 (-6 * 4 + 10y * 4) = -5 (-24 + 40y) = -5 Solving -24 + 40y = -5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 40y = -5 + 24 Combine like terms: -24 + 24 = 0 0 + 40y = -5 + 24 40y = -5 + 24 Combine like terms: -5 + 24 = 19 40y = 19 Divide each side by '40'. y = 0.475 Simplifying y = 0.475
| 7x+3=4x+66 | | x=2,1/35/9 | | 8/2+5(7-3) | | 9/4+(3/4x+2)^2=0 | | 10x-2=25x+1 | | 3a+6b=18 | | 3t-2= | | -2x+2-4=-2(-x+4) | | 2(3x-5)=-11 | | -2=-(2n-8) | | (8x^3-8x^2-26x-10)/(2x-5) | | 69-5x=22x+24 | | 14+3y=17 | | 25=z/-3 | | x*10-18=52 | | -5(m-4)=12 | | ln(x-3)=ln(5x)+ln(2) | | a/7+12=9 | | 7-8x=76-29x | | 3a-9whena=5 | | -4x-40-6=-3x+6 | | -512^1/3 | | 3/5+x=2/3 | | 3(x+6)=10 | | 48a-21-8= | | 5z+3=28 | | -7+9y+5n-4y-3n-29= | | -7x+3=-9x+7 | | x-2/13=9/13 | | 14-5(3x-7)=-26 | | (4ba^2)(a^4b^0)= | | 25-12x=13 |